2019
DOI: 10.31616/asj.2018.0231
|View full text |Cite
|
Sign up to set email alerts
|

Factors Impacting Mortality in Geriatric Patients with Acute Spine Fractures: A 12-Year Study of 613 Patients in Singapore

Abstract: Study Design Retrospective database analysis. Purpose To identify risk factors that predict mortality following acute spine fractures in geriatric patients of Singapore. Overview of Literature Acute geriatric spinal fractures contribute significantly to local healthcare costs and hospital admissions. However, geriatric mortality following acute spine fractures is scarcely assessed in the Asian population. Methods E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Gutiérrez-González et al reported that age, male sex, oncological history, and comorbidity were independent risk factors for post-spinal fracture mortality [ 16 ]. Soon et al found that mobility status and the presence of old compression fractures were also factors that influence spinal fracture mortality [ 4 ]. Our study was the first to compare risk factors of mortality in spine fractures compared to hip fractures.…”
Section: Discussionmentioning
confidence: 99%
“…Gutiérrez-González et al reported that age, male sex, oncological history, and comorbidity were independent risk factors for post-spinal fracture mortality [ 16 ]. Soon et al found that mobility status and the presence of old compression fractures were also factors that influence spinal fracture mortality [ 4 ]. Our study was the first to compare risk factors of mortality in spine fractures compared to hip fractures.…”
Section: Discussionmentioning
confidence: 99%
“…Mortality is increased markedly in older male patients or in cases in which the fracture is associated with neurologic deficit, the most common cause of death being pneumonia, followed by ischemic heart disease and cancer. 15,16…”
Section: Discussionmentioning
confidence: 99%
“…Mortality is increased markedly in older male patients or in cases in which the fracture is associated with neurologic deficit, the most common cause of death being pneumonia, followed by ischemic heart disease and cancer. 15,16 The first step in the management of these patients is recognition and diagnosis of an unstable vertebral fracture. Spinal instability is defined in the literature as a worsening deformity or displacement of the spine that compromises neurologic status of the patient and changes with time or as the inability of the spine under physiologic loads to maintain relationship between vertebrae.…”
Section: Discussionmentioning
confidence: 99%
“…Such fractures have become a common cause and cause of death in elderly fracture patients [5][6][7][8].…”
Section: Discussionmentioning
confidence: 99%